Towards Open Knowledge : The State of World Bank Knowledge Services - World Bank (Washington, DC, 2014)
This first World Bank Knowledge Report launches what is intended as a series of World Bank Knowledge Reports. Although knowledge is a fundamental to the Bank s overall mission, and informs all of the Bank s development activities, it has not received the same degree of attention from management that has been accorded to its lending activities. By paying attention to knowledge work as a distinct service, the Bank and our stakeholders will be able to better understand the results of that work. This will lead to better management of the knowledge production process, more strategic partnerships with other knowledge institutions, and greater operational and policy impact. As the first in the series, this report spends some time surveying the horizon describing what kind of knowledge activities the World Bank undertakes and what its experience with this type of work has been. Consultations within the Bank and with external reviewers and partners during preparation of the report have enabled the institution to speak more clearly about the full range of these activities, and how they are evolving in response to changing conditions in the world and the changing demands of clients. In terms of the way forward, this first Knowledge Report makes some specific recommendations for measuring results and opening many of the Bank s processes to more external inputs. The report also identifies important issues that will become part of ongoing conversations, both within the Bank and with clients and external partners. This volume is a synthesis of inputs from a variety of studies and units across the Bank. These are covered in significantly greater detail in a Background Report, which may be of greatest interest to Bank staff and managers who want a more in-depth understanding.